Effect of Purified Rabbit Anti-Salmonella typhimurium Antibodies on the Fate of Intravenously Injected Bacteria - Schulkind, Martin L. (1971)
Purified IgM and IgG antibodies to Salmonella typhimurium “O” antigen were prepared from rabbit serum collected “early” (6 to 8 days) and “late” (30 to 32 days) during the course of the immune response. The effect which these passively administered antibodies had upon the reticuloendothelial organ sequestration of intravenously injected (125)I-labeled heat-killed S. typhimurium in nonimmune rabbits was studied. In the absence of specific antibody, the spleen (per gram) sequestered more organisms than did the liver, kidneys, and lungs. In the presence of “early” antibody to S. typhimurium, sequestration of organisms in the spleen was two to three times greater than sequestration in the spleen of animals that had received “late” antibody to S. typhimurium, heterologous antibody or no antibody. Although “late” antibody did not increase sequestration of organisms in the spleen, it did result in a per gram liver sequestration of bacteria which was two times greater than that observed in animals that had received “early” antibodies to S. typhimurium, heterologous antibody or no antibody. The presence of passively administered antibody had no detectable effect upon the sequestration of bacteria in the kidneys and the lungs. Thus, it would seem that antibodies isolated early in the immune response increase the efficiency of splenic sequestration of blood-borne particulate material, whereas “late” antibody favors sequestration in the liver.